2022
DOI: 10.1177/03635465211062910
|View full text |Cite
|
Sign up to set email alerts
|

High Body Mass Index Does Not Adversely Affect Outcomes in High-Level Athletes Undergoing Primary Hip Arthroscopy: A Propensity-Matched Comparison With Minimum 2-Year Follow-up

Abstract: Background: The effect of high body mass index (BMI) on outcomes in athletes has not been established. Purpose: (1) To report minimum 2-year patient-reported outcome (PRO) scores and return to sports (RTS) for high-level athletes with high BMI undergoing hip arthroscopy for femoroacetabular impingement syndrome (FAIS) and (2) to compare results with a propensity-matched control group of high-level athletes with a normal BMI. Study Design: Cohort study; Level of evidence, 3. Methods: Data were collected on all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…4 Although the BMI was well below the threshold for obesity, previous literature has reported that higher BMIs may not be associated with worse short-term outcomes after hip arthroscopy. 22 Interestingly, the present study reports high rates of cartilage damage, with over 30% of the athletes exhibiting ALAD grade 3 or 4 damage. This is consistent with a recent study by Owens et al, 40 who reported that basketball athletes at midterm outcomes exhibited >30% ALAD grade 3 or 4 damage and had a 3.6% conversion rate to THA.…”
Section: Discussionmentioning
confidence: 47%
“…4 Although the BMI was well below the threshold for obesity, previous literature has reported that higher BMIs may not be associated with worse short-term outcomes after hip arthroscopy. 22 Interestingly, the present study reports high rates of cartilage damage, with over 30% of the athletes exhibiting ALAD grade 3 or 4 damage. This is consistent with a recent study by Owens et al, 40 who reported that basketball athletes at midterm outcomes exhibited >30% ALAD grade 3 or 4 damage and had a 3.6% conversion rate to THA.…”
Section: Discussionmentioning
confidence: 47%
“…With respect to calibration intercept and probability estimation, the algorithm was comparable and tended to overestimate the observed proportion of patients who achieved the MCID at 2 years at lower predicted probabilities (<0.4 in both studies). This may be partially explained by (1) the reproducibility and efficacy of hip arthroscopy procedures, (2) the higher median preoperative HOS-SS scores observed in the external validation sample, and (3) the observation of consistent functional improvements for these patients in the study populations and throughout the hip arthroscopy literature studying athletic populations 5,7,8,13,28 ; however, at higher probabilities (between 0.6 and 0.80), the algorithm in the current external validation study tended to slightly underestimate the observed proportion of patients who achieved the MCID at 2 years by up to 20% (Figure 2), while calibration remained good to excellent in this range in the development study. 13 This underestimation may be partially explained by the external validation sample size being smaller than the development study sample size despite statistical calculations confirming that the current sample size was sufficient.…”
Section: Discussionmentioning
confidence: 98%
“…Fourth, the type of injury was self-reported and within each report there may be a varying level of severity that was unable to be captured in this study. Fifth, Jimenez et al 21 noted that current PROs may not be able to accurately reflect the changes in function or status for a predominantly active population. As such, future studies with specific PROs targeted to assess adolescents may be beneficial when conducting further analysis comparing outcomes based on type of injury.…”
Section: Discussionmentioning
confidence: 99%
“…It is considered as the optimal method for group comparisons according to prior literature. 21 Hips were matched using R (Version 4.1.0; R Foundation for Statistical Computing) until no further matches could be made.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation